FLOATING DRUG DELIVERY OF ANTIDIABETIC DRUGS: AN OVERVIEW - MEGHA SHARMA; SEEMA KOHLI (International Journal of Pharma and Bio Sciences, 2012)
Despite the tremendous advancement in drug delivery, oral route remains the preferred route for the administration due to higher levels of patient compliance. But conventional forms offer no control over drug delivery, leading to fluctuations in plasma drug level. These have a disadvantage of a release all or nothing emptying process while the multiple unit particulate system pass through the gastrointestinal tract to avoid the vagaries of gastric emptying and thus release the drug more uniformly. Floating drug delivery systems (FDDS) are one of the important categories with gastric retentive behavior. Incorporation of the drug in a controlled release gastroretentive dosage forms, can remain in the gastric region for several hours which significantly prolong the gastric residence time, improve bioavailability, reduce drug waste and enhance the solubility of drugs. Several approaches are currently utilized including FDDS, swelling and expanding systems, polymeric bioadhesive systems, high-density and low-density systems, modified-shape systems and other delayed gastric emptying devices. Various low density polymers as cellulose acetate, chitosan, eudragit, acrycoat, methocil, polyacrylates, polyvinyl acetate, carbopol, agar, polyethylene oxide, polycarbonates, acrylic resins and polyethylene oxide cellulose are utilized for formulation of floating drug delivery. These systems are useful to several problems encountered during the development of a pharmaceutical dosage form. Although there are number of difficulties to be worked out to achieve prolonged gastric retention, a large number of companies are focusing toward commercializing this technique. The present literature review summarizes some FDDS of antidiabetic drugs.